Exploring Pharmacokinetic interactions between SHR8554, a µ-opioid receptor biased agonist, and Itraconazole in healthy Chinese subjects - Lei Huang; Hao Jiang; Yuanyuan Huang; Juan Li (Scientific Reports)
Abstract SHR8554 is a biased agonist for µ-opioid receptors, which was under investigation as an alternative therapy for clinical pain. This open, fixed-sequence study evaluated its pharmacokinetic (PK) interaction with itraconazole, a strong CYP3A4 inhibitor. Subjects (n = 16) were given SHR8554 (1 mg) intravenously on Day 1 and Day 9, and itraconazole capsules (200 mg) twice a day orally from Day 4 to Day 10. Liquid chromatography tandem mass spectrometry was applied for plasma concentration of SHR8554. After single dose of SHR8554, the Cmax and Tmax were 16.69 ± 3.48 ng/mL and 0.16 h, which was quite close to that of combination dose of itraconazole (Cmax 16.58 ± 8.79 ng/mL, Tmax 0.22 h). AUC0−∞ under monotherapy (18.37 ± 3.61 ng∙h/mL) and combinated therapy (19.91 ± 3.59 ng∙h/mL) were also approximate to each other. The main PK parameters were almost consistent between single dose of SHR8554 period and itraconazole combined period with the geometric mean ratios (90%CI) basically within 80–125%. Treatment-emergent adverse events occurred much less in single dose period than combination period (75.0% vs. 93.8%). Therefore, when co-administered with CYP3A4 inhibitors, SHR8554 maintained its distinctive PK profile while the subjects experienced an increase in symptoms associated with opioid receptor activation. The ClinicalTrials.gov identifier is NCT05928988 (03/07/2023).